1997
DOI: 10.1007/bf02778061
|View full text |Cite
|
Sign up to set email alerts
|

Elements in the pathophysiology of diminished growth hormone (GH) secretion in aging humans

Abstract: Remarkable decreases in growth hormone (GH) secretion accompany healthy aging. The pathophysiology of this hyposomatotropism is confounded by concurrent changes in body composition (with increased visceral fat), physiological declines in estrogen and androgen concentrations, differences in gender responses to aging, and alterations not only in the quantity of GH secreted, but also (as more recently evident) in the orderliness or regularity of the GH release process (e.g., as assessed by approximate entropy). I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
3

Year Published

2001
2001
2010
2010

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(22 citation statements)
references
References 74 publications
1
18
0
3
Order By: Relevance
“…It has recently been reported that, in transgenic GHRH-green fluorescent protein mice, aging does not decrease GHRH but causes an enlargement of GHRH-positive axons suggestive of neuropeptide accumulation (2). It has been suggested, and confirmed in our laboratory, that GHRH-receptor (GHRH-R) mRNA levels in the pituitary decline with age (24), which is in agreement with the age-related decline of pituitary GHRH sensitivity, although there is no general consensus on this point (10,50,61). Because GHRH-R is upregulated by the hypothalamic GHRH (21), our previous findings suggest that a major event in the decline of GH might be the decrease of hypothalamic GHRH secretion.…”
supporting
confidence: 75%
“…It has recently been reported that, in transgenic GHRH-green fluorescent protein mice, aging does not decrease GHRH but causes an enlargement of GHRH-positive axons suggestive of neuropeptide accumulation (2). It has been suggested, and confirmed in our laboratory, that GHRH-receptor (GHRH-R) mRNA levels in the pituitary decline with age (24), which is in agreement with the age-related decline of pituitary GHRH sensitivity, although there is no general consensus on this point (10,50,61). Because GHRH-R is upregulated by the hypothalamic GHRH (21), our previous findings suggest that a major event in the decline of GH might be the decrease of hypothalamic GHRH secretion.…”
supporting
confidence: 75%
“…These findings suggest a disruption of the GH-IGF1 axis activity based on a change in regular sleep pattern with this disease (54), or that this could be an effect of the small sample size. Although 1 month of sham ventilation induced elevated IGF1 levels (55), normalization of sleep pattern induced a restoration of the GH axis activity.…”
Section: Discussionmentioning
confidence: 82%
“…It exerts direct effect on protein and on carbohydrate and lipid metabolism, and controls the rate of skeletal and visceral growth (Salomon et al, 1996;Tsoshima T, 1998; Russell-Jones and Umpleby 1999). For reasons not yet fully understood, GH secretion gradually declines during normal aging (Corpas et al, 1993;Veldhuis et al, 1997). This decline with age reflects changes in both frequency and magnitude of secretory pulses.…”
Section: Introductionmentioning
confidence: 99%